The microRNA-449 family inhibits TGF-β-mediated liver cancer cell migration by targeting SOX4 - Sandbothe, Maria; Buurman, Reena; Reich, Nicole; Greiwe, Luisa; Vajen, Beate; Gürlevik, Engin; Longerich, Thomas; Rössler, Stephanie; Schirmacher, Peter (Journal of hepatology, 2017)
Background & Aims: Modulation of microRNA expression is a potential treatment for hepatocellular carcinoma (HCC). Therefore, the epigenetically regulated microRNA-449 family (miR-449a, miR-449b, miR-449c) was characterized with regards to its functional effects and target genes in HCC. Methods: After transfection of miR-449a, miR-449b, and/or miR-449c, tumor-relevant functional effects were analyzed using in vitro assays and a xenograft mouse model. Binding specificities, target genes, and regulated pathways of each miRNA were identified by microarray analyses. Target genes were validated by luciferase reporter assays and expression analyses in vitro. Furthermore, target gene expression was analyzed in 61 primary human HCCs compared to normal liver tissue. Results: Tumor suppressive effects, binding specificities, target genes, and regulated pathways of miR-449a and miR-449b differed from those of miR-449c. Transfection of miR-449a, miR-449b, and/or miR-449c inhibited cell proliferation and migration, induced apoptosis, and reduced tumor growth to different extents. Importantly, miR-449a, miR-449b, and, to a lesser degree, miR-449c directly targeted SOX4, which codes for a transcription factor involved in epithelial-mesenchymal transition and HCC metastasis, and thereby inhibited TGF-β-mediated cell migration. Conclusions: This study provides detailed insights into the regulatory network of the epigenetically regulated miRNA-449 family and, for the first time, describes distinct tumor suppressive effects and target specificities of miR-449a, miR-449b, and miR-449c. Our results indicate that particularly miR-449a and miR-449b may be considered for miRNA replacement therapy to prevent HCC progression and metastasis. Lay summary: In this study, we demonstrated that the microRNA-449 family acts as a tumor suppressor in liver cancer by causing cell death and inhibiting cell migration. These effects are caused by downregulation of the oncogene SOX4, which is frequently overexpressed in liver cancer. We conclude that the microRNA-449 family may be a target for liver cancer therapy.